Pharmacological and genetic approaches to downregulate FIS1 mitigate neuropathic pain - Zhu, Chang-Lei; Li, Shu-Jiao; Lin, Zhi-Peng; Ni, Zi-Wei; Tian, Ke; Xia, Yu-Lu; Tie, Jing-Jing; Pu, Xue-Yin; Huang, Yun-Qiang; Wu, Fei-Fei; Liu, Hui; Zhang, Kun-Long; et al. (The Journal of neuroscience, 2025)
Despite the established link between neuropathic pain and abnormal mitochondrial fission in neurons, the specific role of mitochondrial fission protein 1 (FIS1) in this process remains to be fully elucidated. In this study, the subjects we investigated were 6-8-week-old male mice. Comprehensive behavioral tests and immunostaining, along with Western blot analysis, revealed that neuropathic pain induced by spared nerve injury (SNI) upregulated FIS1 expression in the spinal cord dorsal horn (SC-DH). Furthermore, artificially upregulated FIS1 in SC-DH caused hyperalgesia behaviors in normal mice, while downregulation alleviated neuropathic pain. Using GAD2-MITO and vGluT2-MITO transgenic mice, we found that mitochondria network of both excitatory and inhibitory neurons in the SC-DH were disrupted. Selective downregulation of FIS1 in excitatory neurons via vGluT2-Cre mice reversed mitochondrial impairments and alleviated neuropathic pain. Network pharmacological prediction analysis combined with pharmacological tests indicated that compounds capable of downregulating FIS1 expression, such as epigallocatechin gallate (EGCG), the primary bioactive component of tea polyphenols, may possess analgesic properties. In contrast, cinnamic acid (CA), an organic acid derived from cinnamon bark, did not exhibit the capability to downregulate FIS1 expression and consequently lacked analgesic efficacy. Our research findings suggest that FIS1 may represent a novel molecular target for the treatment of neuropathic pain. Significance Statement Neuropathic pain is closely related to abnormal mitochondrial fission, but the mechanism remains unclear. This study shows that SNI-induced neuropathic pain leads to increased expression of FIS1 in the spinal cord dorsal horn (SC-DH). Upregulation of FIS1 in the SC-DH causes hyperalgesia, while downregulation alleviates neuropathic pain. In the pain state, mitochondrial network in both excitatory and inhibitory neurons in the SC-DH are disrupted. Downregulation of FIS1 in excitatory neurons of the SC-DH can improve mitochondrial dysfunction and thereby alleviate neuropathic pain. Network pharmacology combined with pain-related behaviors suggest that the epigallocatechin gallate (EGCG) can relieve neuropathic pain by inhibiting FIS1 in the SC-DH. In conclusion, FIS1 may be a novel molecular target for the treatment of neuropathic pain.